Christian Discourses of the Holy and the Sacred from the 15th to the 17th Century - Hiergeist, Teresa; del Olmo, Ismael (Peter Lang, 2020)
The chapters reconstruct the values, norms, experiences, material manifestations, and power structures underlying the understandings of the holy and the sacred in early modern Christian contexts. They intend to gain a characteristic profile of the associated concepts and ideas, persons and social groups, objects and texts, times and spaces, and behaviours and performances, in order to provide insights into the identities and hegemonic structures developed around them. They trace the interdependence of religion and society, highlighting the constructiveness, transformability, and diversity of the sacred culture from the 15th to the 17th century.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Europa 1450-1700; Frühe Neuzeit; Sakralkultur